2015
DOI: 10.5296/emsd.v4i2.8036
|View full text |Cite
|
Sign up to set email alerts
|

Screening Assessment of Cyanobacteria and Cyanotoxins in Southern California Lentic Habitats

Abstract: Harmful bloom-forming cyanobacteria (CyanoHABs) and associated toxins are increasingly prevalent world-wide. We conducted a screening-level study to determine if cyanobacteria and associated cyanotoxins were present in Southern California coastal lakes, ponds, and seasonally tidal lagoons. We evaluated waterbody nutrient status and physiochemical parameters, land use, waterbody type, and habitat type, to determine their utility as screening factors for risk of CyanoHAB blooms. One-time grab samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Similarly, cyanobacteria were ubiquitous in a screening assessment of 30 lakes, depressional wetlands and coastal lagoons in southern California, with Microcystis spp. dominant in 96% of study sites [ 39 ]. Quantification of cyanotoxins in that study were limited, however, microcystins were detected in high concentrations at 10% of sites that exceeded both the California recreational health thresholds, and the World Health Organization guidance for human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cyanobacteria were ubiquitous in a screening assessment of 30 lakes, depressional wetlands and coastal lagoons in southern California, with Microcystis spp. dominant in 96% of study sites [ 39 ]. Quantification of cyanotoxins in that study were limited, however, microcystins were detected in high concentrations at 10% of sites that exceeded both the California recreational health thresholds, and the World Health Organization guidance for human health.…”
Section: Introductionmentioning
confidence: 99%
“…Microcystins were the focus of the current study due to the dominance of Microcystis spp. in previous screening assessments [ 38 , 39 ], and because microcystins are the most common cyanotoxin detected in lakes in the U.S. [ 51 ]. Three separate field surveys were conducted: (1) an ambient probability based assessment of depressional wetlands (2011–2013); (2) a screening assessment of lakes, reservoirs and coastal lagoons determined to be at significant risk for blooms in 2013; and (3) an ad hoc bloom event response survey in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanotoxins were detected at concentrations that frequently exceeded California recreational health thresholds ( Table 1 ) and were persistently detected throughout the study period. The cyanotoxin concentrations detected during this study are currently the highest recorded concentrations of microcystins, anatoxin-a, and cylindrospermopsin in southern California lakes and estuaries ( Magrann et al, 2015 ; Howard et al, 2017 ; Tatters et al, 2019 ), and among the highest reported within California lakes ( Kudela, 2011 ). The sea otter mortality event reported in Miller et al (2010) documented microcystin concentrations in Pinto Lake of 2,900 μg L −1 , substantially lower than the maximum concentrations detected in Lake Elsinore.…”
Section: Discussionmentioning
confidence: 69%
“…In California, evidence is mounting that cyanotoxins constitute considerable health risks downstream from their freshwater sources. Cyanotoxins have been detected in a wide array of lentic and lotic ecosystems in California including lakes, reservoirs, depressional wetlands, coastal lagoons, estuaries, streams, and rivers (Bouma‐Gregson, Kudela, et al, 2018; Drake et al, 2010; Fetscher et al, 2015; Graham et al, 2020; Howard et al, 2017, 2021; Izaguirre et al, 2007; Kelly et al, 2019; Kudela, 2011; Loftin, Graham, et al, 2016; Magrann et al, 2015; Tatters et al, 2017, 2019). Additionally, benthic freshwater cyanobacterial proliferations, including several toxin‐producing cyanobacterial species, have been identified throughout California waterways and regionally (Bouma‐Gregson, Kudela, et al, 2018; Bouma‐Gregson, Olm, et al, 2018; Bouma‐Gregson et al, 2019; Fetscher et al, 2015; Kelly et al, 2019; Izaguirre et al, 2007), although understanding of the factors that promote benthic blooms is limited (see review Wood et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies conducted in Monterey Bay, California, using passive samplers (see Recommendation 2) revealed that downstream transport of MCs was an issue throughout several watersheds (not just from a single waterbody), with MCs detected in several outflows into the Monterey Bay National Marine Sanctuary (Gibble & Kudela, 2014). Studies conducted in other areas of California have also detected cyanotoxins at the land-sea interface indicating that these occurrences have existed but have gone largely undocumented (Howard et al, 2017;Magrann et al, 2015;Peacock et al, 2018;Tatters et al, 2017Tatters et al, , 2019Tatters et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%